2011
DOI: 10.2174/1876517301103010001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factor α and Manganese Superoxide Dismutase Polymorphisms in Patients with Non-Alcoholic Steatohepatitis from Northeast Mexico

Abstract: Background and Aims: Environmental and genetic factors play a role in the pathogenesis and natural history of non-alcoholic steatohepatitis (NASH). The aim of this study was to determine if the G-238A (allele TNFA) and G-308A (allele TNF2) tumor necrosis factor-alpha (TNF-) and Ala9Val manganese superoxide dismutase (MnSOD) polymorphisms were associated with NASH in a case-control study of subjects from Northeast Mexico. Methods: We analyzed DNA samples from 68 patients with NASH (50 women and 18 men; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Our results agree with the results of Trujillo-Murillo et al, who reported that the frequency of the -238 TNF-α polymorphism was significantly higher in NASH patients than in controls (29% vs 12%; p value = 0.0047) [47]. The study by Valenti et al also found a higher frequency of -238 polymorphisms but not of the -308 TNF polymorphisms in Italian patients with NAFLD [43].…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with the results of Trujillo-Murillo et al, who reported that the frequency of the -238 TNF-α polymorphism was significantly higher in NASH patients than in controls (29% vs 12%; p value = 0.0047) [47]. The study by Valenti et al also found a higher frequency of -238 polymorphisms but not of the -308 TNF polymorphisms in Italian patients with NAFLD [43].…”
Section: Discussionsupporting
confidence: 92%
“…Candidate gene studies have identified several polymorphisms in the TNF-α gene promotor (Qidwai and Khan, 2011). The higher prevalence of the TNF-α/-238 promotor polymorphism in NAFLD or NASH patients, compared to controls, are reported in the Italian (Valenti et al, 2002), Mexican and Chinese (Hu et al, 2009;Zhou et al, 2010;Trujillo-Murillo et al, 2011) cohorts. In the Japanese, two other polymorphisms have instead been identified, -1031C and -863A (Tokushige et al, 2007).…”
Section: Cardiomyopathy Tumour Necrosis Factormentioning
confidence: 99%
“…Valenti L et al 17 Huang J et al 18 Tokushige K et al 19 Wong VW et al 20 Hu ZW et al 21 Zhou YJ et al 23 Trujillo-Murillo K et al 24 Total (95% CI) Total events Heterogeneity: Chi² = 9.22, df = 6 (P = 0.16); I² = 35% Test for overall effect: Z = 5.33 (P < 0.00001) ated with insulin resistance and increased body mass index (BMI) in NAFLD patients, contributing to the pathogenesis of NAFLD. Chinese researchers 21,23 also demonstrated an association between -238 A allele (TNFA) polymorphism and increasing serum TNF-a in Chinese patients with NAFLD.…”
Section: Study or Subgroupmentioning
confidence: 99%